How well does Miscanthus ensile for use in an anaerobic digestion plant?. (May 2016) - Whittaker, Carly; Hunt, John; Misselbrook, Tom; Shield, Ian
Abstract: This study examined the ability for early-harvested Miscanthus ( Miscanthus x giganteus and Miscanthus sacchariflorus ) to be stored in silage for later use in anaerobic digestion. Two silage additives favouring a homo and hetero-fermentation pathway were examined. The results show that silage additives are necessary to effectively ensile Miscanthus, otherwise untreated Miscanthus grasses incurred dry matter losses of 4% during three months' storage. The silage additives improved the lactic and acetic acid production in the Miscanthus silages however did not have any effect on the biogas yield. On a 'per tonne volatile solids'-basis, Miscanthus produces half the biogas yield of maize. The outlook for the use of Miscanthus AD therefore depends on the yield when harvested in autumn. A minimum yield of 19–26.5 t DM/ha is needed for Miscanthus to match the biogas production from a similar area of maize yielding 10–14 t DM/ha. Highlights: The silage and biomethane potential of Miscanthus was examined. Silage additives are necessary to effectively ensile Miscanthus . Improved lactic and acetic acid production did not improve the biomethane potential. The biomethane potential for Miscanthus in anaerobic digestion depends on its yield.